Insertion professionnelle, socialisation des jeunes français « sans qualification » et formation par alternance - Maéva Duchène; Christine Poplimont
To what extend can dual programs in general and French work experience integration programs in particular effectively solve problems raised by the double logic of transition from education into working life for young people without qualification? While in the 70s it was necessary to help them find a job, very quickly political policies havec had to take into account a second integration necessity: a social integration or socialization, as a precondition to professional integration. Apart from the lack of qualification, these young people suffer several factors of social marginalization which prevent them from acceding to the labour market. In this paper, we study a French learning by doing integration model which appears to be relevant for disadvantaged young people on the labour market, insofar as its implementation fulfill some essential conditions.